Chocolate mousse: Physical chemistry in the formative itinerary of the new high school - Peixoto, Sandra Cadore; Silva, Maximilian Oliveira da; Lima, Roberta Medianeira dos Santos (Seven Editora, 2023)
The teaching of Natural Sciences becomes increasingly demanding in the sense that students can assimilate scientific knowledge. The experimental activity of Physical Chemistry, in the school environment, constitutes a space that enhances the cognitive and educational aspects of the students. In this sense, the formative itineraries must guarantee the appropriation of knowledge, as well as the use of methodologies that favor the protagonism of youth. For the development of this work, a documentary research was carried out in the references that guide the teaching of physical chemistry, considering the New High School. For this, the study of the National Common Curricular Base and the Gaucho Curricular Reference was carried out, as well as the research in scientific articles about the teaching of physical chemistry in basic education. This proposal fits into the curricular arrangement Natural Sciences and its technologies, in the structuring axis Scientific Investigation, and aims to teach the concepts of physical chemistry, through the production of a classic chocolate mousse. The target audience was students of the 2nd year of High School. In this work it was decided to produce a classic chocolate mousse, as an experimental strategy to learn and teach physical chemistry. Within the three specific competencies of the Area of Natural Sciences and its Technologies, it can be observed that Chemistry is present in all specific skills, whether in the form of Organic Chemistry, Inorganic Chemistry, Physical Chemistry or Analytical Chemistry. Thus, chemical experimentation in the school environment provided the student to relate the objects of study of physical chemistry through observations, comparisons, generalizations and conclusions, integrating theoretical knowledge into the context of everyday life. DOI:https://doi.org/10.56238/ptoketheeducati-008